Image-Guided Versus Conventional Brachytherapy for Locally Advanced Cervical Cancer: Experience of Single Institution with the Same Practitioner and Time Period - Lee, Tae Hoon; Kim, Kyung Su; Kim, Hak Jae; Choi, Chang Heon; Kang, Seonghee; Eom, Keun-Yong; Wee, Chan Woo; Song, Yong Sang; Park, Noh Hyun; Kim, Jae-Weon; Chung, Hyun Hoon; Kim, Hee Seung; et al. (Cancer research and treatment, 2023)
Purpose This study aimed to compare treatment outcomes and toxicity profile between imaged-guided brachytherapy (IGBT) versus conventional brachytherapy (CBT) performed by the same practitioner during the same time period.Materials and Methods Medical records of 104 eligible patients who underwent brachytherapy for locally advanced cervical cancer were retrospectively reviewed. Fifty patients (48.1%) underwent IGBT, and 54 (51.9%) patients underwent CBT. All patients underwent concurrent chemoradiation with cisplatin. High-dose-rate intracavitary brachytherapy with dose prescription of 25-30 Gy in 4-6 fractions was performed for all patients. Late lower gastrointestinal (GI) and urinary toxicities occurred more than 3 months after the end of brachytherapy were included for comparative and dosimetric analyses.Results The median follow-up period was 18.33 months (range, 3.25 to 38.43 months). There were no differences in oncologic outcomes between the two groups. The IGBT group had lower rate of actuarial grade ≥ 3 toxicity than the CBT group (2-year, 4.5% vs. 25.7%; p=0.030). Cumulative equieffective D2cc of sigmoid colon was significantly correlated with grade ≥ 2 lower GI toxicity (p=0.033), while equieffective D2cc of rectum (p=0.055) and bladder (p=0.069) showed marginal significance with corresponding grade ≥ 2 toxicities in the IGBT group. Half of grade ≥ 3 lower GI toxicities impacted GI tract above the rectum. Optimal thresholds of cumulative D2cc of sigmoid colon and rectum were 69.7 Gy and 70.8 Gy, respectively, for grade ≥ 2 lower GI toxicity.Conclusion IGBT showed superior toxicity profile to CBT. Evaluating the dose to the GI tract above rectum by IGBT might prevent some toxicities.